2018
DOI: 10.1016/j.jfda.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Elemental profile and oxygen isotope ratio ( δ 18 O) for verifying the geographical origin of Chinese wines

Abstract: The elemental profile and oxygen isotope ratio (δO) of 188 wine samples collected from the Changji, Mile, and Changli regions in China were analyzed by inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma optical emission spectroscopy (ICP-OES) and isotope ratio mass spectrometry (IRMS), respectively. By combining the data of δO and the concentration data of 52 elements, the analysis of variance (ANOVA) technique was firstly applied to obtain the important descriptors for the discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 46 publications
0
38
0
2
Order By: Relevance
“…In the LDA, δD is identified as the 6th discriminator. Other studies that use δ 18 O and elemental analyses found that δ 18 O contributes significantly to regional discrimination in wines from Brazil, Romania, China and Italy (Dinca et al, 2016, Dutra et al, 2011, Fan et al, 2018, Raco et al, 2015). It was unclear, however, if δD was measured in these studies.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the LDA, δD is identified as the 6th discriminator. Other studies that use δ 18 O and elemental analyses found that δ 18 O contributes significantly to regional discrimination in wines from Brazil, Romania, China and Italy (Dinca et al, 2016, Dutra et al, 2011, Fan et al, 2018, Raco et al, 2015). It was unclear, however, if δD was measured in these studies.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Note that a maximum of 6 comparison pairs are possible for the 4 regions. In many studies world-wide, Mn and Rb have proven to be important independent classifiers (Durdic et al, 2017, Fan et al, 2018, Pepi and Vaccaro, 2018, Taylor et al, 2003). In the present study, only Mn is used in LDA, where it appears as the first classifier, separating CA from SA (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…В качестве идентифицирующих критериев предлагаются показатели, как непосредственно связанные с качественными характеристиками винопродукции (в частности, компоненты углеводно-кислотного [1,2], фенольного [3,4], ароматобразующего [5,6] комплексов), так и показатели, взаимосвяь которых с качеством продукции весьма опосредована или не доказана (аминокислотный, катионно-анионный состав, редкоземельные и микроэлементы [7][8][9][10], соотношениz изотопов 87 Sr/ 86 Sr, 13 с/ 12 с, 18 о/ 16 о [11][12][13] и др. Чаще всего современнные подходы к идентификации происхождения вин базируются на измерении системы показателей [14][15][16].…”
unclassified